Impact of real-time glucose monitoring using FreeStyle Libre 3 on glycaemia in type 2 diabetes managed with basal insulin plus SGLT2 inhibitor and/or GLP-1 agonist: the FreeDM2 randomised controlled trial protocol - Gerry Rayman; Thomas Yates; Ramzi A Ajjan; Patrick Moore; Pratik Choudhary; Thozhukat Sathyapalan; Parth Narendran; Ahmed Iqbal; Rachel Ann Elliott; Sankalpa Neupane; Mark Evans; Hood Thabit; et al. (BMJ Open)
Introduction Effective management of type 2 diabetes mellitus (T2DM) consists of lifestyle modification and therapy optimisation. While glycaemic monitoring can be used as a tool to guide these changes, this can be challenging with self-monitoring of blood glucose (SMBG). The FreeStyle Libre 3 (FSL3) is a real-time continuous glucose monitoring (CGM) system designed to replace SMBG. The evidence for the benefit of CGM in people with T2DM on non-intensive insulin regimens is limited. This study aims primarily to assess the glycaemic impact of FSL3 in people with suboptimally controlled T2DM treated with basal-only insulin regimens plus sodium-glucose cotransporter-2 (SGLT-2) inhibitor and/or glucagon-like peptide (GLP)-1 agonist.Methods and analysis This is an open-label, multicentre, parallel design, randomised (2:1) controlled trial. Recruitment has been offered across 24 clinical centres in the UK and nationally through self-referral. Adults with T2DM treated with basal-only insulin regimens plus SGLT-2 inhibitor and/or GLP-1 agonist and with screening HbA1c from ≥59 mmol/mol to ≤97 mmol/mol are included. Eligible participants will be randomised to either FSL3 (intervention) for 32 weeks or continuation of SMBG (control). The study is split into two phases, each of 16 weeks duration: phase 1 consisting of self-management with basal-insulin self-titration and phase 2 where additional therapies may be initiated. Control group participants may subsequently enter an optional extension phase to receive FSL3. The primary endpoint is the difference between treatment groups in mean change from baseline in HbA1c at 16 weeks. Secondary outcomes include HbA1c at 32 weeks, CGM-based metrics, therapy changes, physical activity levels and psychosocial measures. An economic evaluation for costs and patient outcomes will be undertaken.Ethics and dissemination The study was approved by the Health Research Authority, Health and Care Research Wales and the West Midlands-Edgbaston Research Ethics Committee (reference: 23/WM/0092). Study results will be disseminated in peer-reviewed journals.Trial registration number NCT05944432.Secondary identifying number Identifier assigned by the sponsor: ADC-UK-PMS-22057.Protocol version Revision D. Dated, 13 December 2024.